THE EFFECT OF WOMEN’S PER CAPITA EXPENDITURE AND WOMEN’S EXPECTED YEARS OF SCHOOLING ON THE NUMBER OF POOR PEOPLE IN INDONESIA: A HUMAN RESOURCE MANAGEMENT PERSPECTIVE - Muhammad Iqbal Al Farizi; Achmad Efendi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the influence of women’s per capita expenditure and women’s expected years of schooling on the number of poor people in Indonesia. The research uses a quantitative approach with secondary time-series data obtained from official publications of the Badan Pusat Statistik covering the period 2014–2024. The data were analyzed using multiple linear regression after conducting classical assumption tests to ensure the reliability of the model. The results show that women’s per capita expenditure has a negative influence on poverty, indicating that higher levels of women’s economic welfare tend to reduce the number of poor people. Meanwhile, women’s expected years of schooling show a positive but not significant relationship with poverty. Overall, both variables together contribute to explaining variations in poverty levels. These findings suggest that improving women’s economic conditions plays an important role in poverty reduction efforts. However, this study is limited by the relatively short observation period. Therefore, future research is recommended to expand the observation period and include additional variables to obtain more comprehensive results regarding the factors influencing poverty in Indonesia. Keywords: Women’s Per Capita Expenditure; Expected Years of Schooling; Poverty; Human Resource Development